Nitrogen acquisition, fixation and transfer in maize/alfalfa intercrops are increased through root contact and morphological responses to interspecies competition - SHAO, Ze-qiang; ZHENG, Cong-cong; POSTMA, Johannes A.; LU, Wen-long; GAO, Qiang; GAO, Ying-zhi; ZHANG, Jin-jing (Journal of Integrative Agriculture, 2021)
Nitrogen (N) fixation by legumes and nitrogen transfer to cereals have been considered as important pathways for overyielding and higher N use efficiency in cereal/legume intercropping systems. However, the extent to which root morphology contributes to N fixation and transfer is unclear. A two-factorial greenhouse experiment was conducted to quantify the N fixation, transfer and root morphology characteristics of the maize/alfalfa intercropping system in two consecutive years using the 15N-urea leaf labeling method, and combining two N levels with three root separation techniques. N application could inhibit N fixation and transfer in a maize/alfalfa intercropping system. Irrespective of the N application level, compared with plastic sheet separation (PSS), no separation (NS) and nylon mesh separation (NNS) significantly increased the total biomass (36%) and total N content (28%), while the N fixation rate also sharply increased by 75 to 134%, and the amount of N transferred with no root barrier was 1.24–1.42 times greater than that with a mesh barrier. Redundancy analysis (RDA) showed that the crown root dry weight (CRDW) of maize and lateral root number (LRN) of alfalfa showed the strongest associations with N fixation and transfer. Our results highlight the importance of root contact for the enhancement of N fixation and transfer via changes in root morphology in maize/alfalfa intercropping systems, and the overyielding system was achieved via increases in maize growth, at the cost of smaller decreases in alfalfa biomass production.